Tantalum half-Heusler alloys RbTaSi and RbTaGe: potential candidates for desirable thermoelectric and spintronic applications. Issue 11 (1st March 2023) - Ganie, Nisar Ahmad; Mir, Shabir A.; Gupta, Dinesh C.
Abstract : Variations in molar susceptibility ( χ ) and inverse of susceptibility ( χ −1 ) with temperature signify the presence of ferromagnetic nature. Abstract : Heusler alloys have drawn the interest of researchers due to their possible technical significances and multifunctional use. Herein, a thorough theoretical analysis using "density functional theory (DFT)" is performed to investigate the general physical features of RbTaSi and RbTaGe alloys. The "generalised gradient approximation (GGA)" and "Tran–Blaha modified Becke–Johnson (TB-mBJ) potential" has been incorporated to model the electronic structures of RbTaSi and RbTaGe. The structural optimization results signify that these materials are stable in the ferromagnetic phase with a cubic F 4̄3 m structure, which is supported by the computed elastic parameters. In addition, cohesive energy and microhardness signify strong bonding. The spin-polarisation bands and density of states indicate the half-metallic nature of these materials. These materials have spin magnetic moment 2μB, thereby emphasizing the use of these alloys for spintronic applications. Transport and thermodynamic properties have been calculated, and their temperature dependence is illustrated. The behavior of transport coefficients with temperature futher implies the presence of half-metallic nature.